Won’t You be My Neighbor: How Epithelial Cells Connect Together to Build Global Tissue Polarity - Cote, Lauren E.; Feldman, Jessica L. (Frontiers in Cell and Developmental Biology, 2022)
Epithelial tissues form continuous barriers to protect against external environments. Within these tissues, epithelial cells build environment-facing apical membranes, junction complexes that anchor neighbors together, and basolateral surfaces that face other cells. Critically, to form a continuous apical barrier, neighboring epithelial cells must align their apico-basolateral axes to create global polarity along the entire tissue. Here, we will review mechanisms of global tissue-level polarity establishment, with a focus on how neighboring epithelial cells of different origins align their apical surfaces. Epithelial cells with different developmental origins and/or that polarize at different times and places must align their respective apico-basolateral axes. Connecting different epithelial tissues into continuous sheets or tubes, termed epithelial fusion, has been most extensively studied in cases where neighboring cells initially dock at an apical-to-apical interface. However, epithelial cells can also meet basal-to-basal, posing several challenges for apical continuity. Pre-existing basement membrane between the tissues must be remodeled and/or removed, the cells involved in docking are specialized, and new cell-cell adhesions are formed. Each of these challenges can involve changes to apico-basolateral polarity of epithelial cells. This minireview highlights several in vivo examples of basal docking and how apico-basolateral polarity changes during epithelial fusion. Understanding the specific molecular mechanisms of basal docking is an area ripe for further exploration that will shed light on complex morphogenetic events that sculpt developing organisms and on the cellular mechanisms that can go awry during diseases involving the formation of cysts, fistulas, atresias, and metastases.